PENGARUH BELANJA DAERAH DAN PENDAPATAN ASLI DAERAH TERHADAP BESARAN BANTUAN KEUANGAN PROPINSI KABUPATEN/ KOTA DI KALIMANTAN BARAT - B21111056, Mat Romli (Jurnal Pembangunan dan Pemerataan, 2016)
This thesis entitled "Influence of Revenue Expenditure Budgets and Revenue Amount of Financial Aid Against areas Province". Objectives 1. examine and analyze the effect of public revenue and expenditure budgets to the amount of financial assistance in the districts / cities in West Kalimantan Province, 2. examine and analyze the amount of local revenues to the provincial financial assistance in the districts / cities in West Kalimantan Province. The method used in this research is quantitative by using the data that is data panel of financial aid and local revenues from 2009 to 2013. Processing by using a software program economics views (E-views). The results of the discussion concluded that based on the t-statistic shopping areas have a significant impact on the amount of financial assistance to and local revenues have a significant impact on the financial aid besarasn province From this study it can be concluded that financial assistance is strongly influenced by regional expenditure and revenue.